Synthesis and Humidity Sensing Properties of NiO Intercalated Polyaniline Nanocomposite. Issue 2 (22nd January 2019) - Singh, Pratibha; Kushwaha, Chandra Shekhar; Shukla, S.K.; Dubey, G.C.
ABSTRACT: The exercising cooperative and interfacial properties of metal oxide and conducting polymer as a sensing material for humidity detection was the focal point of this study. In this piece of work nano sized NiO and its composite with polyaniline has been prepared. The cooperative effects of NiO on stuructural, morphology, humidity sensing behaviour of PANI has been investigated. Prepared materials were characterized by infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscope (SEM), UV–VIS spectroscopy and Four probe techniques. The result reveals that the NiO strongly influences on polymer chain, crystallinity, stability, electrical and optical properties of PANI, which improves its viability in technology development. Finally, PANI/NiO was used for electrochemical humidity sensing of a closed atmosphere. The result reveals that 100 times increase in sensitivity of PANI due to the presence of NiO nano particles. Finally, the results indicate that the impact of NiO on PANI makes it promising perspective materials for humidity monitoring of closed chamber with improved sensing parameters over several method and materials. Graphical Abstract: